Filsafat Pendidikan dalam al-Qur’an: Dari Penciptaan Manusia ke Edukasi Komunikasi - Sujiat Zubaidi (Universitas Darussalam Gontor, 2018)
This article sheds light on obtaining the comprehensive interrelated study about the philosophical dimensions of education in the Qur’an in its various aspects. Because the spectrum of education in the Qur’an has a diverse horizon that we fnd it in several verses. Al-Qur’an is the pre eternal translator of the mighty book of the universe, the post eternal interpreter of the various tongues reciting the verses of creation; the commentator of the book of the Worlds of Seen and the Unseen. The revealer of the treasuries of the divine names hidden in the heavens and on the earth. Actually, that the education dimension we can explore on the creation of human beings with various terminology and the phase of its creation, even the terminology revealed by the Qur’an also implies the existence of education principles. Moreover, the existence of educational logic as a reﬂection of integrative education that we fnd in the chosen and inspirational word which in the contents of ‘Ulûm al-Qur’ân named i‘jâz lughawiy. In addition, that educational element in the repetition of words and stories is more interesting, as the dialogue contained in the Qur’an; both between God and His creations and between human and others, like parents’ dialogue with their children. In this article, the author also describes another aspect, namely the various principles of communication revealed by the Qur’an with a variety of symbols comprehensively; named qawlan karîman, qawlan sadîdan, qawlan ma‘rûfan and others